Social Rehabilitation Practices of Inclusion In The Educational Process In Working With Children With Disabilities - Vasylyeva-Khalatnykova, Maryna O. (2021)
Coming into being and development of inclusive education in contemporary Ukrainian society are analysed. The tasks of educational institutions in creating an inclusive space are defined, and the approaches to work with children with disabilities are identified. Works of foreign and domestic scholars and practitioners who studied the problems of inclusion of children with disabilities in the educational process and in the context of social rehabilitation activities are studied. Emphasis is placed on theoretical analysis of social rehabilitation practices of inclusion. A mechanism for implementing social rehabilitation practices of inclusion in the educational process of working with children with disabilities is suggested.